Preface of AJDHM's First Issue - ASEAN Journal of Disaster Health Management (Universitas Gadjah Mada, 2025)
The ASEAN Journal of Disaster Health Management aims to provide a dedicated platform for professionals, researchers, and policymakers to share insights and innovative approaches to managing health challenges arising from disasters. In this inaugural issue, we bring together a diverse collection of nine articles that reflect the shared commitment of our contributors to improving disaster preparedness, response, recovery, and resilience.